Answer :

3x^{2} + px + 4 = 0

3(2/3)^{2} + p(2/3) + 4 = 0

4/3 + 2p/3 + 4 = 0

p = -8

3x^{2} - 8x + 4 = 0

By middle term splitting,

3x^{2} - 6x - 2x + 4 = 0

x = 2/3 or x = 2

Hence, x = 2

**OR**

α + β = 5 ----(1)

α – β = 1 ----(2)

Solving (1) and (2), we get

α = 3 and β = 2

also, αβ = 6

or 3(k - 1) = 6

k – 1 = 2

k = 3

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Which of the follRS Aggarwal - Mathematics

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics